Undiagnosed senile systemic amyloidosis with mesenteric angiopathy leading to fatal outcomes: Two case series with a review of literature - Avneesh Gupta; Maryna Tarbunova; Anil Aggrawal; Anges E Aysola (Wolters Kluwer Medknow Publications, 2017)
Amyloid mesenteric angiopathy is difficult to diagnose as gastrointestinal (GI) signs are nonspecific and radiological studies rarely identify amyloid deposits with certainty. The objective of this study was to highlight the pathological findings of amyloid mesenteric angiopathy in cases of senile systemic amyloidosis. Literature review, author's research data, and practice experience were used. Systemic amyloidosis should be considered in the differential diagnoses when evaluating nonspecific and unexplained GI in patient population aged> 55 years to decrease the morbidity and fatal outcomes.